The Secondary School Biological Science Curriculum of Odisha A Critical Study - Mohanty, Gitanjali (JOURNAL OF INDIAN EDUCATION, 2012)
The study spreading over 31 secondary schools, and involving 31 biological science teachers, 143 students (60 boys and 83 girls) and 10 experts and educationists, is an attempt to discover and reflect facts about the biological science curriculum at the secondary level in the State of Odisha and improve the effectiveness. The study revealed many shortfalls like absence of laboratory in almost all the schools, textbooks with many deficiencies, want of appropriate and adequate teaching aids, non-performance of co-scholastic activities, absence of access to community resources, lack of initiative to visit places of biological and scientific importance in order to connect knowledge to life outside the school and to make learning more practical rather than textbookcentric. The educationists interviewed voiced concern regarding the existing process of evaluation needs improvement as felt by eminent educationists. The curriculum transactions in the schools did not indicate the input of the intended curriculum to be operationalised in real sense of the term. The operational aspect of curriculum needs be emphasized in its right perspective so as to provide benefit to learners.